Critical issues in mission among tribals - Longkumer, Awala (Delhi & Nagpur ISPCK & NCCI, 2011)
Papers presented at the National Council of Churches in India, Tribal and North East India Pre-Assembly, held at Shillong during 27-30 April 2008.
Papers presented at the National Council of Churches in India, Tribal and North East India Pre-Assembly, held at Shillong during 27-30 April 2008
Includes bibliographical references.
Keywords: Church work with the poor -- India, Northeastern -- Congresses; Missions -- India, Northeastern -- Congresses; India, Northeastern -- Scheduled tribes -- Social conditions -- Congresses; India, Northeastern -- Scheduled tribes -- Economic conditions -- Congresses